Law Enforcement In Overcoming Election Crime (Case Study Of Bawaslu, Semarang District) - Redhi Setiadi; Megawati Barthos; Zudan Arief Fakrulloh (Publikasi Indonesia, 2023)
The issues with upholding election law must be resolved comprehensively if elections are to be held in an honest and fair manner and if they are not to be delegitimized in the future. The first thing that must be done is to determine what is causing issues with law enforcement; After that, a comprehensive solution to this issue is sought, resulting in the establishment of a system of election law enforcement capable of guaranteeing free and fair elections. According to international democratic election standards, free and fair elections can be achieved if there are legal instruments that can protect organizers, participants, candidates, voters, observers, and citizens in general from fear and intimidation, violence, bribery, fraud, and other fraudulent practices that will affect the results of the election. This type of research is normative research. The approach used is a statutory approach (statute approach) and a conceptual approach (conceptual approach). Secondary data are used as the data source. Qualitative and descriptive methods were used to analyze the data. Conclusions are drawn using the deductive method, namely concluding from general to specific, especially those related to the research topic, namely law enforcement against election crimes. This research resulted in findings that future election legislation must re-clarify the notion of election administration violations. In this case, administrative violations can be divided into two major groups, namely minor administrative violations, and serious administrative violations.